MOTIVASI MAHASISWA STUDI DI JURUSAN IPI UIN SUNAN KALIJAGA YOGYAKARTA - , DINA FANI GUSTIANI, SE, Prof. DR. Mudiyono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
UIN Sunan Kalijaga Yogyakarta provides library training known as Graduate Program (S1) Ilmu Perpustakaan dan Informasi (IPI) to outcome librarians who are acadamically and professionally competent in the fields of library and information science. For the last three years, the student enrollment has been increased. This research is to find out the motivation of students for studying at IPI, as well as to analyze the studentsâ perception and expectation. Descriptive method and cualitative approach are used for this research. The informants are nine students of IPI, who are on sixth and ninth semester